Musculoskeletal Tumor Profile in Saiful Anwar General Hospital Malang from January 2011-December 2017 - Satria Pandu Persada Isma; Istan Irmansyah Irsan; Brian Dhananjaya (Fakultas Kedokteran Universitas Lambung Mangkurat, 2018)
Abstract: Primary tumours of musculoskeletal tissues are relatively uncommomn, they represent only 1% of all malignancies in all ages groups, but the incidence is arising each year. Many medical research and experiments were developed to found appropriate methods of treatment for tumor patients. Mortality rates of malignant musculoskeletal tumor patients still higher than benign cases. The aim of this study was to describe the incidence, age and sex distribution, location and histology of benign and malignant musculoskeletal tumors diagnosed and/or treated at a tertiary referral Orthopaedic Department serving the East Java. This was a retrospective analysis of prospectively collected data of medical records of all patients diagnosed and/or treated for any type of musculoskeletal tumor at Orthopaedic and Traumatology Department of Saiful Anwar Hospital, in the period from January 2011 to December 2017. This study resulted there were 531 cases of musculoskeletal tumor, within the characteristic: the peak of incidence occurs in the patient older than 60; the highest case was Osteosarcoma (92 cases); and breast metastases (40 cases) distributed highest mortality rates for metastastic bone tumor patients. Result of this study was people at age 60 and older have higher risk for Muskulokeletal Tumor, and Osteosarcoma was the most frequent case. Keywords: Musculoskeletal tumor, data based system, incidence, East Java